ANALISIS MANAJEMEN PENDAPATAN PRODUKSI USAHATANI PADI DESA SUNGAI NILAU DITINJAU DARI PERSPEKTIF ISLAM - Sari, Suci Wulan; Isma, As’ad; Sudharyati, Neneng (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the application of income management carried out by the people of Sungai Nilau Village in increasing income and to find out the factors of production used in the farming of the Sungai Nilau Village. This research is a qualitative type using primary and secondary data sources. The results of the study show that there are several indicators applied by the community who carry out rice farming in Sungai Nilau Village as follows: Setting targets, then determining strategies, determining strategies can produce or earn income according to the target, setting standards of success, every rice farming actor must able to meet their self-imposed standard of success within a set timeframe as well. Then several factors of production increase income or influence income increase, namely, the cost of production, the level of production owned and donated in the production process, the amount of labor used in a farming activity greatly influences the income of the farming business, and the size of the capital. owned by farmers will affect the income earned.